Intravenous enoxaparin as alternative ECMO anticoagulation over a period of 94 days: a case report - Durila, Miroslav; Berousek, Jan; Vlasakova, Vlasta; Vymazal, Tomas (Journal of cardiothoracic surgery, 2023)
BACKGROUND: Unfractionated heparin is used worldwide as a standard anticoagulation therapy for extracorporeal membrane oxygenation (ECMO) machines. However, its use brings about significant bleeding and thrombotic complications for critically ill patients. This case report shows that low molecular weight heparin together with ECMO-produced primary haemostasis pathology can be used as an alternative way of ECMO anticoagulation. CASE PRESENTATION: This paper presents the case of a patient with respiratory failure who subsequently suffered from cardiac failure and spent 94 days on combined V-V and V-A ECMO devices (two ECMO devices running simultaneously on one patient) with intravenous enoxaparin used instead of unfractionated heparin anticoagulation. No life-threatening bleeding/thrombotic events happened during this period, nor did any technical problems with ECMO occur. CONCLUSIONS: In this case report, continuous intravenous low molecular weight heparin anticoagulation was used as a safe alternative to ECMO anticoagulation.
Keywords: LMWH; mimotělní membránová oxygenace; trombóza; krvácení; enoxaparin; Heparin; Thrombosis; ECMO; antikoagulancia; Humans; Extracorporeal Membrane Oxygenation; Anticoagulants; Enoxaparin; Extracorporeal membrane oxygenation; Hemorrhage; heparin; Heparin, Low-Molecular-Weight; PFA 200; Primary haemostasis; heparin nízkomolekulární; lidé